Interactive Learning Multimedia: A Shortcut for Boosting Gen-Z’s Digital literacy in Science Classroom - Siti Zahra Mulianti Natsir; Bibin Rubini; Didit Ardianto; Nurhaedah Madjid (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop interactive multimedia learning to sharpen Gen- Z’s digital literacy on the material of substance pressure. The method used is research and development with research instruments including multimedia validation sheets, digital literacy questionnaires, teachers’ response questionnaires, and Gen- Z response questionnaires. The research began with need analysis, then continued with the multimedia design stage. The multimedia design stage produces the first draft of multimedia and research instruments. The first draft of the multimedia was validated at the development stage. The development stage included the validation of multimedia and research instruments, as well as a limited field test.  A valid Multimedia was subsequently implemented into science learning. The evaluation stage was carried out by administering a questionnaire on digital literacy questionnaires and teachers’ and students’ response questionnaires. The results showed that learning multimedia was declared feasible based on a content validity value of 100%, and Gen - Z’s digital literacy index obtained a score of 3.30 or was in the medium category. It can be concluded that interactive learning multimedia can be an alternative way in enhancing Gen-Z's digital on-substance pressure materials. This study shows that science learning can contribute to accelerating digital transformation by enhancing youths’ capacity in digital literacy